A study of the classification of the mandibular arch forms in a Filipino sample population using the MBT appliance - Zhang, Zebiao
The achievement of a stable, functional, and esthetic arch form has long been one of the prime objectives of orthodontics. A key aspect in the achievement of this goal was the identification of a suitable arch form to use in the treatment of each case. For over a century, researchers have been trying to define the "ideal" arch form, and various solutions to this problem have been proposed, but few have stood the test of time. More recently, with the advancements in the preadjusted appliance systems, the application of the MBT(with TM superscript) pre-selected arch form guides have made it easier and less time consuming to do some minor modifications associated with individual variations in the human arch form. The Filipino sample was examined to determine whether a particular MBT arch form type (tapered, ovoid, square) could be identified and conform to a specific type of Angle's malocclusion. A total of a hundred and five mandibular casts of Filipino adults were classified as Class I with N=35, Class II with N=35 and Class III with N=35 malocclusion groups.Four linear measurements of the mandibular dental arches were performed and two independent ratios were determined. A TESA Digit-Cal caliper was used to measure the photocopied images of the study casts to the nearest 0.001 mm accuracy.